Depletion and Dysfunction of Dendritic Cells: Understanding SARS-CoV-2 Infection - Chang, Teding; Yang, Jingzhi; Deng, Hai; Chen, Deng; Yang, XiangPing; Tang, Zhao-Hui (Frontiers in Immunology, 2022)
Uncontrolled SARS-CoV-2 infection is closely related to the innate immune disorder and the delayed adaptive immune system. Dendritic cell (DC), which bridges innate immunity and adaptive immunity, plays an excellent role in defending against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). In this review, we summarize the latest updates concerning the role of DCs in SARS-CoV-2 infections, with particular focuses on the complex interplay modes between DCs and SARS-CoV-2 which includes pyroptosis-induced activation, RAAS system activation and C-type lectin DC-specific intercellular adhesion molecule-grabbing non-integrin (DC-SIGN)-mediated activation. During SARS-CoV-2 induces DCs activation, the decline numbers, the impaired antigen presentation capability and the deficiency of type I interferon (IFN-I) production of DCs were observed in many severe SARS-CoV-2 infected patients. This article enumerates all possible mechanisms for the pathological activation of DCs in order to understand the pattern of SARS-CoV-2 infection. Here we illustrate these various aspects of depletion and dysfunction of DCs in anti-SARS-CoV-2 infection and also provide a brief overview of novel antiviral vaccination and IFN-I therapy based on DCs targeting.